Effects of Electroacupuncture on the Cortical Extracellular Signal Regulated Kinase Pathway in Rats with Cerebral Ischaemia/Reperfusion. Issue 6 (December 2017) - Wu, Chunxiao; Li, Chun; Zhou, Guoping; Yang, Lu; Jiang, Guimei; Chen, Jing; Li, Qiushi; Zhan, Zhulian; Xu, Xiuhong; Zhang, Xin
Objective: To explore the effects of electroacupuncture (EA) on the phosphorylated extracellular signal regulated kinase (p-ERK) pathway of the cerebral cortex in a rat model of focal cerebral ischaemia/reperfusion (I/R). Methods: 160 adult Sprague-Dawley rats underwent middle carotid artery occlusion (MCAO) to establish I/R injury and were randomly divided into four groups (n=40 each) that remained untreated (I/R group) or received EA at LU5, LI4, ST36 and SP6 (I/R+EA group), the ERK inhibitor PD98059 (I/R+PD group), or both interventions (I/R+PD+EA groups). An additional 40 rats undergoing sham surgery formed a healthy control group. Eight rats from each group were sacrificed at the following time points: 2 hours, 6 hours, 1 day, 3 days and 1 week. Neurological function was assessed using neurological deficit scores, morphological examination was performed following haematoxylin-eosin staining of cortical tissues, and apoptotic indices were calculated after terminal deoxyribonucleotidyl transferase (TdT)-mediated biotin-16-dUTP nick-end labelling. Cortical protein and mRNA expression of p-ERK and ERK were measured by immunohistochemistry and real-time quantitative PCR, respectively. Results: Compared with the I/R group, neurological deficit scores and apoptotic indices were lower in the I/R+EA group at 1 and 3 days, whereas mRNA/protein expression of ERK/p-ERK was higher in the EA group at all time points studied. Conclusion: Our results suggest that EA can alleviate neurological deficits and reduce cortical apoptosis in rats with I/R injury. These anti-apoptotic effects may be due to upregulation of p-ERK. Moreover, apoptosis appeared to peak at 1 day after I/R injury, which might therefore represent the optimal time point for targeting of EA.